Molecular epidemiology of Legionnaires' disease in Israel. (9th December 2013) - Moran‐Gilad, J.; Mentasti, M.; Lazarovitch, T.; Huberman, Z.; Stocki, T.; Sadik, C.; Shahar, T.; Anis, E.; Valinsky, L.; Harrison, T. G.; Grotto, I.; ESCMID Study Group for Legionella Infections (ESGLI); et al.
Abstract National surveillance of Legionnaires' disease (LD) is important to inform control measures and facilitate international networking for timely reporting. This study is the first to describe the molecular epidemiology of LD in Israel. Case notifications for 2006–2011, collated through mandatory reporting, were identified and demographic, clinical and laboratory data were extracted. Unrelated clinical and environmental Legionella pneumophila strains were characterized using standard procedures, Dresden panel of monoclonal antibodies and the ESCMID Study Group for Legionella Infections (ESGLI) Sequence‐Based Typing scheme. In all, 294 cases were reported (crude incidence 0.67 cases/100 000; age‐standardized incidence 1/100 000). LD epidemiological trends and features largely resembled those of the EU, except for a larger proportion of nosocomial cases. Of 28 clinical and 23 environmental strains analysed, 71.4% and 21.7% were serogroup (sg) 1 and the most common immunological subgroup was OLDA/Oxford (64%). Of the clinical strains, OLDA/Oxford, ST1 was the most common (43%) followed by Allentown/France, ST40 (14%). The unusual sg 3 ST338 was found in 17.4% of environmental strains. Novel STs were detected amongst 23.5% of strains. These findings warrant further molecular investigation. Molecular epidemiology data generated from neighbouring countries newly adopting the ESGLI typing scheme for L. pneumophila contribute to understanding of regional strain diversity.